Antimicrobial activity of three different endodontic sealers on the enterococcus faecalis and lactobacillus (in vitro) - Maryam Ehsani; Ata Adibi; Ehsanollah Moosavi; Atana Dehghani; Soraya Khafri; Elham Adibi (Babol University of Medical Sciences, 2013)
Introduction: Growth and proliferation of the remaining microorganisms within the root canals may destroy the surrounding tissue of the root and leads to periapical lesion. Consequently, the complete elimination of microorganisms from the root canal is a n important goal of endodontic therapy. Endodontic sealers do not provide complete seal in root canal system, and micro spaces have always remained between the material and canal walls that lead to penetration of these spaces, so, an antibacterial activity is essential for sealers. The aim of the present study was the in vitro evaluation of antimicrobial activity of the three endodontic sealers on two microorganisms . Methods: To study the effect of each sealer AH26, MTA Fillapex and ADseal on Enterococcus Faecalis and L actobacillus bacteria 10 samples were considered. In this experimental study, 60 plates were exposed to bacteria and 10 plates were considered for control group. Sealer antibacterial effect on bacterial growth was studied after 48 hours. Firstly, the freshly prepared sealers were poured inside the micro tube and diffused in the wall of the micro tube. Then solution of nutrient broth was poured into a micro tube and the determined volume of solution of bacterial suspension was added into a microtube and was kept 24 hours in the incubator to grow the bacteria. Then, it was poured in the plates of blood agar and cultured after 24 hours and then the colonies grown on the plates were counted in sufficient light. The data were analyzed with M ANOVA statistical test and SPSS Version 18. Results: Most bacteria grew in the plates of ADseal sealer and MTA fillapex sealer with means of 5113.00CFU and 3077.00CFU respectively, while the lowest number of bacteria grew in the plates of AH26 sealer with a mean of 1345.15CFU. Conclusions: Most antibacterial activities of each enterococcus faecalis and l actobacillus bacteria sample was for AH26 sealer and MTA fillapex sealer. The lowest antibacterial activity was for ADseal sealer.